The possible application of virtual reality for managing anxiety in athletes - Trpkovici, Melinda; Makai, Alexandra; Prémusz, Viktória; Ács, Pongrác (Frontiers in Sports and Active Living, 2025)
IntroductionOne of the most effective techniques is “stress inoculation” training (SIT), which is increasingly utilized to reduce anxiety and enhance athletic performance. The aim of our research was to investigate the extent to which the stress situation we created in virtual reality evokes psychological responses in athletes, compared to the responses they experience during a competitive match.MethodsThe sample consisted of 24 female athletes with an average age of 18.71 ± 5.42 years. Of these, 9 were elite basketball players, 8 were table tennis players, and 7 were handball players. All participants completed the Athlete Anxiety Questionnaire, designed to measure anxiety in high-stakes situations and assess levels of concentration and self-confidence during matches. Additionally, within the virtual reality environment we created, athletes were exposed to stress-inducing factors scientifically proven to elicit stress responses. Paired-sample t-tests were used to examine differences between measurements (match and virtual reality scenario), and ANOVA tests were used to compare differences between athletes groups (basketball players, table tennis players and handball players).ResultsOur findings indicated that the sports stress scenario simulated in virtual reality triggers stress responses in athletes comparable to those experienced during actual competitive matches. No significant difference was detected in any factor between the total scores of the tests completed after the virtual reality session and those completed after the match (p > 0.05). The greatest impact of VR on cognitive anxiety was observed regarding the fear of mental block or choking during a match, received an average score higher than that of the match (1.75 ± 1.032 vs. 1.38 ± 0.711 respectively, p = 0.04)ConclusionBased on these results, we can conclude that the sports stress scenario generated by virtual reality can indeed induce a comparable level of stress in athletes compared to actual matches. Therefore, virtual reality technology shows promise as a tool for enhancing athletes' stress management skills and could be a significant asset in sports psychology preparation processes.